OntoNegli : uma ontologia no domínio das doenças negligenciadas - Oliveira, Aldo Sergio de (2011)
Knowledge is an important tool for any entity, person or country. Rather than have the knowledge, the sharing becomes crucial in the quest for qualification, continuation and improvement. As in other areas, the representation of knowledge is important in the health sector. Thus, our objective is to create an ontology for the representation of knowledge on public health, specifically on neglected diseases. To achieve this goal, it was shaped and developed an ontology for that domain, so that computer systems can use it to assist in medical decision making. Based on the study of documents and interviewing experts, ontology was modeled following the methodology 101 and using the Protégé tool. The ontology created is composed of 53 classes and 38 properties that represent knowledge covering the types of diseases considered to be neglected in Brazil, clinical manifestations, symptoms, causes of disease vectors, types of tests for diagnosis of these forms of transmission, etc.. To evaluate the ontology, were initially created the most important classes of individuals, then they were defined and executed queries about symptoms for diseases and their diagnoses. A questionnaire applied to experts, evaluated the responses of the ontology, showing that it contributes to the diagnosis of neglected diseases.